Treatment of a Cellulose Fiber Surface with a Suberin Monomer-Derived Polymer. Issue 3 (August 2015) - Li, Dongfang; Iversen, Tommy; Ek, Monica
The biorefinery concept requires the development of value-added products, such as materials from biomass, including bark. Suberin is the most abundant component in birch (Betula verrucosa) outer bark and acts as a barrier against the penetration of water and external attacks from microorganisms. The aliphatic domain of suberin is rich in hydroxy fatty acids, such as cis-9, 10-epoxy-18-hydroxyoctadecanoic acid. In this study, it was isolated from the outer bark of birch and polymerized to prepare polyepoxy acid (PEA), which was used to impregnate filter papers. After complete drying, PEA-loaded filter papers were placed under UV to crosslink the epoxides through cationic polymerization with a diaryliodonium salt as the photo-initiator. The crosslinking was evaluated using Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC). The materials obtained after UV curing showed substantially increased hydrophobicity, decreased moisture absorption, increased tensile strength, and increased ductility. Field-emission scanning electron microscopy (FE-SEM) showed that the crosslinked PEA covered the surface of the cellulose fibers and filled the interstitial spaces.